The convergence of financial systems in Europe - Reinhard H. Schmidt; Andreas Hackethal; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2001)
Since the beginning of the 1990s, it has been widely expected that the implementation of the European Single Market would lead to a rapid convergence of Europe's financial systems. In the present paper we will show that at least in the period prior to the introduction of the common currency this expected convergence did not materialise. Our empirical studies on the significance of various institutions within the financial sectors, on the financing patterns of firms in various countries and on the predominant mechanisms of corporate governance, which are summarised and placed in a broader context in this paper, point to few, if any, signs of a convergence at a fundamental or structural level between the German, British and French financial systems. The German financial system continues to appear to be bank-dominated, while the British system still appears to be capital market-dominated. During the period covered by the research, i.e. 1980 – 1998, the French system underwent the most far-reaching changes, and today it is difficult to classify. In our opinion, these findings can be attributed to the effects of strong path dependencies, which are in turn an outgrowth of relationships of complementarity between the individual system components. Projecting what we have observed into the future, the results of our research indicate that one of two alternative paths of development is most likely to materialise: either the differences between the national financial systems will persist, or – possibly as a result of systemic crises – one financial system type will become the dominant model internationally. And if this second path emerges, the Anglo-American, capital market-dominated system could turn out to be the “winner”, because it is better able to withstand and weather crises, but not necessarily because it is more efficient.
urn:nbn:de:hebis:30-18257
Keywords: G1; G2; G10; G30; G34; H55; P51; 330; Financial system; capital market-based financial system; human capital formationbank-based financial system; pension system; risk allocation; Finanzsektor; Finanzsystem; Kapitalstruktur; Corporate Governance; Anpassung; EU-Binnenmarkt; Deutschland; Großbritannien; Frankreich